2022
DOI: 10.3389/fimmu.2022.872458
|View full text |Cite
|
Sign up to set email alerts
|

Skin Interstitial Fluid and Plasma Multiplex Cytokine Analysis Reveals IFN-γ Signatures and Granzyme B as Useful Biomarker for Activity, Severity and Prognosis Assessment in Vitiligo

Abstract: BackgroundThe course of vitiligo is unpredictable, with periods of disease flare-ups and prolonged recovery periods. It is essential to establish a biomarker profile as a substitute marker for disease activity to predict disease activity, severity, and prognosis prediction. The use of localized skin interstitial fluid as biomarkers has recently gained interest, but extensive studies of the association between skin interstitial fluid, plasma, and the disease course is lacking. This study aims to evaluate the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In contrast, epidermal immune cells, such as endogenous T cells, Langerhans cells, and γδ T cells, are not required ( 112 ). IFN-γ inhibits melanogenesis and directly induces melanocyte apoptosis ( 113 ). A recent single-cell sequencing study of vitiligo showed that fibroblast pairs from different sites IFN-γ responsiveness determine its ability to recruit CD8 + T cells.…”
Section: New Therapeutic Strategies In Vitiligo Immunometabolismmentioning
confidence: 99%
“…In contrast, epidermal immune cells, such as endogenous T cells, Langerhans cells, and γδ T cells, are not required ( 112 ). IFN-γ inhibits melanogenesis and directly induces melanocyte apoptosis ( 113 ). A recent single-cell sequencing study of vitiligo showed that fibroblast pairs from different sites IFN-γ responsiveness determine its ability to recruit CD8 + T cells.…”
Section: New Therapeutic Strategies In Vitiligo Immunometabolismmentioning
confidence: 99%
“…Furthermore, chemo-attractant cytokines play a pivotal role in recruiting leukocytes to inflammatory sites, amplifying the inflammatory reaction, and inducing melanocyte death [ 11 ]. Serum cytokine levels can be measured for monitoring disease severity and treatment efficacy in many studies [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%